The DR score in RETeval™ electroretinogram system facilitates expeditious and uncomplicated early detection and assessment of diabetic polyneuropathy in clinical practice - Yukako Sugiura-Roth; Tatsuhito Himeno; Emi Asano-Hayami; Yuriko Asada-Yamada; Miyuka Kawai; Yuka Shibata; Tomohide Hayami; Mikio Motegi; Makoto Kato; Hiromi Nakai-Shimoda; Emiri Yura-Miura; Yoshiaki Morishita; et al. (PLoS ONE, 2025)
Background The principal aim of this investigation was to assess the utility of a novel DR score for the early detection of diabetic polyneuropathy (DPN). This score, currently integrated into the RETeval™ electroretinogram (ERG) system, is derived from parameters such as ERG wave characteristics, patient age, and pupillary response. Traditional nerve conduction studies (NCS), though valuable, have notable limitations, including the necessity for costly equipment and specialized personnel. Consequently, it was postulated that the DR score—initially devised for predicting diabetic retinopathy—might serve as a practical alternative for diagnosing DPN. This study sought to test the hypothesis that the DR score could offer a reliable means of both diagnosing DPN and estimating its severity. Methods The study retrospectively analyzed 82 diabetic patients admitted to Aichi Medical University Hospital between November 2016 and January 2019. ERG was performed using the RETeval™ device, and NCS was conducted to classify DPN stages according to the Baba’s Differentiation Classification (BDC) system. Multiple regression analysis and receiver operating characteristics (ROC) analysis were employed to assess the relationship between the DR score and DPN stages. Results Among 82 participants, 24.4% (n = 20) had no DPN (stage 0), and 75.6% (n = 62) had stage 1 or higher DPN. The DR score was significantly correlated with various clinical parameters, including nerve conduction velocities and the severity of DPN as classified by BDC stages. The regression model showed that both the DR score and age were significant predictors of DPN severity. The ROC analysis demonstrated that the DR score had a moderate ability to discriminate between no DPN and stage 1 or more of DPN, with an area under the ROC curve of 0.738. Conclusions In conclusion, this study involving 82 patients suggests that the DR score may be a valuable tool for the early detection and staging of DPN, potentially offering a more accessible and cost-effective alternative to traditional NCS, with significant implications for improving diabetic care.